Does Extreme Language Control Training Improve Cognitive Control? A Comparison of Professional Interpreters, L2 Teachers and Monolinguals - Van der Linden, Lize; Van de Putte, Eowyn; Woumans, Evy; Duyck, Wouter; Szmalec, Arnaud (Frontiers in Psychology, 2018)
There is currently a lively debate in the literature about whether bilingualism leads to enhanced cognitive control or not. Recent evidence suggests that knowledge of more than one language does not always suffice for the manifestation of a bilingual cognitive control advantage. As a result, ongoing research has focused on modalities of bilingual language use that may interact with the bilingual advantage. In this study, we explored the cognitive control performance of simultaneous interpreters. These highly proficient bilinguals comprehend information in one language while producing in the other language, which is a complex skill requiring high levels of language control. In a first experiment, we compared professional interpreters to monolinguals. Data were collected on interference suppression, prepotent response inhibition, and working memory capacity, using the flanker task, the Simon task, and a digit span task, respectively. The results showed that the professional interpreters performed similarly to the monolinguals on all measures. In Experiment 2, we compared professional interpreters to monolinguals and second language teachers. Data were collected on interference suppression, prepotent response inhibition, attention, working memory capacity, and updating. These cognitive control measures were assessed using three computerized tasks: an advanced flanker task, a Hebb repetition paradigm, and an n-back task. We found converging evidence for our finding that experience in interpreting may not lead to superior interference suppression, prepotent response inhibition, and working memory capacity. In fact, our results showed that the professional interpreters performed similarly to both the monolinguals and the second language teachers on all tested cognitive control measures. We did however find evidence for a (small) advantage in working memory capacity for interpreters relative to monolinguals when analyzing composite scores of both experiments together. Taken together, the results of the current study suggest that interpreter experience does not necessarily lead to general cognitive control advantages. However, there may be small interpreter advantages in working memory capacity, suggesting that this might be an important cognitive control aspect of simultaneous interpreting. The results are discussed in the light of ongoing debates about bilingual cognitive control advantages.